Analisis Kualitas Tidur, Pola Aktivitas Fisik, Massa Otot, Massa Lemak, dan Body Mass Index Pada Member Idachi Fitness - Muhammad Phirous Rauzan; Yati Rohayati; Kuston Sultoni; Jajat Jajat; Adang Suherman; Widy Dewi Nuryanti (Universitas Galuh, 2025)
Physical fitness is an important component in maintaining health and quality of life. This study aims to analyze the relationship between sleep quality, physical activity patterns, muscle mass, fat mass, and body mass index (BMI) in fitness center members. Using a quantitative correlational approach, this study involved 54 participants selected through purposive sampling technique. The instruments used included the Pittsburgh Sleep Quality Index (PSQI), 24h Movement Questionnaire (QMov24h), and body composition measurements using the Karada Scan. The results showed that good sleep quality and involvement in structured physical activity were associated with a more ideal body composition, characterized by higher muscle mass, balanced fat mass, and BMI in the normal category. In contrast, moderate and vigorous physical activity did not show a significant relationship to body composition. These findings emphasize the importance of comprehensive lifestyle management that includes sleep quality, daily activity, and body composition monitoring to achieve optimal fitness.